Pentingnya Menghargai Perbedaan dalam Masyarakat Riau - Suci, Suci; Liyana, Liyana; Grace, Grace; Perawati, Perawati (Indo-MathEdu Intellectuals Journal, 2024)
The importance of respecting differences in Riau society is crucial to create harmony and peace. The people of Riau, which are rich in culture, ethnicity, and religion, need an attitude of mutual respect so that harmony is maintained. By respecting differences, we can build good communication between individuals, reduce conflicts, and increase cooperation in various aspects of life. In addition, appreciation for differences can also enrich our experiences and insights, thereby encouraging innovation and creativity in society. This study aims to explore in depth how respecting differences can affect social stability and harmony in society. The type of research used is a qualitative approach. The data collection technique in this study uses interviews, observations, and documentation studies. Data analysis was carried out through thematic analysis and narrative analysis. The results of the analysis show that through education and open dialogue, the people of Riau can better understand the values of tolerance and mutual respect, which in turn will strengthen the unity and unity of the nation. Thus, respecting differences is not only a choice, but also a necessity to create a harmonious and prosperous society